(untitled) (Religious dialogue and cooperation, 2021)
Following the political developments that took place in Zimbabwe from the 13th to the 24th of November 2017 that marked the end of Mugabe regime (1980-2017) and the inauguration of a new government, one can ponder whether this was a coup or not a coup? But it was very apparent that the people of Zimbabwe were happy and in support of the military operation that was underway. The churches through the Zimbabwe Head of Christian Denominations (ZHOCD) also added their voice in support of the events that were taking place. All these resulted to the swearing in of Mnangagwa as a new President of Zimbabwe. The new government under Mnangagwa has popularised itself as a “new dispensation” to signal a different approach to governance from that of Mugabe. However, the huge task confronting Mnangagwa’s government was to prove its political legitimacy. This paper explored the political role played by ecumenical movements in the ‘new dispensation’ in Zimbabwe. Published documents, pastoral letters, internet sources and fieldnotes were purposively selected and used to glean data for this paper. Through discourse analysis, the paper discovered that the Christian churches operating under the ecumenical body known as Zimbabwe Heads of Christian Denominations (ZHOCD) is openly accusing the Zimbabwe African National Union- Patriotic Front (ZANU-PF) government for the socio-political ills currently affecting the people. By closely analyzing its pastoral letters, one can observe that ZHOCD’s demands on political reforms to the government are no different to those pushed by the opposition party Movement for Democratic Change (MDC). For this reason, this paper concluded that the ecumenical initiatives are not the best political tools in resolving political conflicts in Zimbabwe since they seem to be partisan as we shall see as the paper unfolds.